Distribution of leaf characteristics in relation to orientation within the canopy of woody species - Escudero, Alfonso; Fernández, José; Cordero, Angel; Mediavilla, Sonia (Acta Oecologica, 2013)
Over the last few decades considerable effort has been devoted to research of leaf adaptations to environmental conditions. Many studies have reported strong differences in leaf mass per unit area (LMA) within a single tree depending on the photosynthetic photon flux density (PPFD) incident on different locations in the crown. There are fewer studies, however, of the effects of differences in the timing of light incidence during the day on different crown orientations. Leaves from isolated trees of Quercus suber and Quercus ilex in a cold Mediterranean climate were sampled to analyze differences in LMA and other leaf traits among different crown orientations. Gas-exchange rates, leaf water potentials, leaf temperatures and PPFD incident on leaf surfaces in different crown orientations were also measured throughout one entire summer day for each species. Mean daily PPFD values were similar for the leaves from the eastern and western sides of the canopy. On the western side, PPFD reached maximum values during the afternoon. Maximum leaf temperatures were approximately 10–20% higher on the west side, whereas minimum leaf water potentials were between 10 and 24% higher on the east side. Maximum transpiration rates were approximately 22% greater on the west, because of the greater leaf-to-air vapor pressure deficits (LAVPD). Mean individual leaf area was around 10% larger on the east than on the west side of the trees. In contrast, there were no significant differences in LMA between east and west sides of the crown. Contrary to our expectations, more severe water stress on the west side did not result in increases in LMA, although it was associated with lower individual leaf area. We conclude that increases in LMA measured by other authors along gradients of water stress would be due to differences in light intensity between dry and humid sites.
Keywords: Canopy orientation; leaf morphology; Leaf temperature; Quercus; water potential

Ontogenetic changes in stomatal and biochemical limitations to photosynthesis of two co-occurring Mediterranean oaks differing in leaf life span - Juárez-López, Francisco José; Escudero, Alfonso; Mediavilla, Sonia (Tree Physiology, 2008)
A quantitative analysis was applied to the stomatal and biochemical limitations to light-saturated net photosynthesis under optimal field conditions in mature trees and seedlings of the co-occurring evergreen oak, Quercus ilex L., and the deciduous oak, Q. faginea Lam. Stomatal limitation to photosynthesis, maximal Rubisco activity and electron transport rate were determined from assimilation versus intercellular leaf carbon dioxide concentration response curves of leaves that were subsequently analyzed for nitrogen (N) concentration, mass per unit area, thickness and percent internal air space. In both species, seedlings had a lower leaf mass per unit area, thickness and leaf N concentration than mature trees. The root system of seedlings during their third year after planting was dominated by a taproot. A lower leaf N concentration of seedlings was associated with lower maximal Rubisco activity and electron transport rate and with assimilation rates similar to or lower than those of mature trees, despite the higher stomatal conductances and potential photosynthetic nitrogen-use efficiencies of seedlings. Consequently, stomatal limitation to photosynthesis increased with tree age in both species. In both seedlings and mature trees, a lower assimilation rate in Q. ilex than in Q. faginea was associated with lower stomatal conductance, N allocation to photosynthetic functions, maximal Rubisco activity and electron transport rate, and potential photosynthetic nitrogen-use efficiency but greater leaf thickness and leaf mass per unit area. Tree-age-related changes differed quantitatively between species, and the characteristics of the two species were more similar in seedlings than in mature trees. Despite higher stomatal conductances, seedlings are more N limited than adult trees, which contributes to lower biochemical efficiency.
10.1093/treephys/28.3.367
Keywords: A–ci response curves; biochemical capacity; leaf morphology; leaf N allocation; mature trees; Quercus faginea; Quercus ilex; seedlings; Stomatal conductance